Melatonin Improved Waterlogging Tolerance in Alfalfa (Medicago sativa) by Reprogramming Polyamine and Ethylene Metabolism - Zhang, Qiang; Liu, Xiaofei; Zhang, Zhifei; Liu, Ningfang; Li, Danzhu; Hu, Longxing (Frontiers in Plant Science, 2019)
Melatonin (MT), polyamines (PAs), and ethylene have been suggested to play key roles in plant growth and development in response to environmental abiotic stresses. However, the effect of melatonin on polyamine and ethylene metabolism under waterlogging stress has rarely been elucidated. The main purpose of this study was to investigate the effect of melatonin pretreatment on waterlogging stress in alfalfa. The experiment was arranged into four treatment groups control with water pretreatment (CK-MT), control with melatonin pretreatment (CK+MT), waterlogging pretreated with water (WL-MT) and waterlogging pretreated with melatonin (WL+MT), with three replications. Six-week-old alfalfa seedlings were pretreated with 100 μM melatonin and exposed to waterlogging stress for 10 days. Plant growth rate, different physiological characteristics, and gene expression level were measured. Results showed that waterlogging induced melatonin accumulation, and melatonin pretreatment increased endogenous MT levels for the control and water-logged plants. Waterlogging stress caused a significant reduction in plant growth, chlorophyll content, photochemical efficiency (Fv/Fm) and net photosynthetic rate (Pn), while also causing increased leaf electrolyte leakage (EL) and malondialdehyde (MDA) content. Pretreatment with melatonin alleviated the waterlogging-induced damage and reduction in plant growth, chlorophyll content, Fv/Fm and Pn. Waterlogging stress significantly increased leaf polyamines (Put, Spd, Spm) and ethylene levels, and the increased PAs and ethylene levels are coupled with higher metabolic enzymes and gene expressions. While pretreatment with melatonin further increased Put, Spd and Spm levels, it also decreased ethylene levels under waterlogging, and those increased PAs levels or decreased ethylene levels are regulated by the metabolic enzymes and gene expressions. The results in this study provide more comprehensive insight into the physiological and molecular mechanisms of melatonin-improved waterlogging tolerance in alfalfa. Furthermore, they suggested that melatonin improved waterlogging tolerance in alfalfa at least partially by reprogramming ethylene and PA biosynthesis, attributable to the increased PAs and decreased ethylene levels, which leads to more enhanced membrane stability and photosynthesis as well as less leaf senescence caused by ethylene.